The top 101 cited articles in environmental clean-up: oil spill remediation - Dadrasnia, A.; Shahsavari, N.; Salmah, I. (2015)
The aim of this search was to identify the 101 top cited articles in the field of oil spill remediation. A search was conducted based on a database of the Web of Science included the journal citation reports from 1980 to 2013. The number of citations of the first 101 top cited articles is from 24 to 816. The decades with most top-cited articles published were 2000-2009 (47 articles) and 1990-1999 (37 articles). The most common research area of study was environmental science ecology. All the articles were published in 54 different journals in this category. Journals with the highest number of cited articles were Applied and Environmental Microbiology (10 articles), Environmental Science and Technology (6 articles), Organic Geochemistry (6 articles), Chemosphere (5 articles). Among the top cited articles the mostly named author were Sakkata Y, and Uddin MA with 6 of articles, followed by Fedorak PM with 5. Out of 101 top cited articles, 14, 13 and 12 articles originated from Canada, USA and France, respectively. Okayama and Alberta Universities were the most common productive institutions. Based on our knowledge, this is the first report of the 101 top cited articles in this category.